Inside Back Cover: Label‐free monitoring and manipulation of microfluidic water‐in‐oil droplets (View 4/2020). Issue 4 (2nd December 2020) - Frey, Christoph; Pfeil, Jonas; Neckernuss, Tobias; Geiger, Daniel; Weishaupt, Klaus; Platzman, Ilia; Marti, Othmar; Spatz, Joachim P.
Abstract : In article number 20200101, Tobias Neckernuss, Ilia Platzman, Joachim P. Spatz and coworkers demonstrate high speed, label‐free droplet sorting based on multiple decision criteria for droplet microfluidics.